Money Supply Rules and Exchange Rate Dynamics - Juha Tervala (Aboa Centre for Economics (ACE), 2010)
This paper examines the implications of monetary policy rules for exchange rate dynamics. I extend a standard New Open Economy Macroeconomics model with the introduction of a simple money supply rule, whereby central banks change their monetary policy if output diverges from potential output or if inflation diverges from the target inflation. A key result is that, in the case of permanent technology and monetary shocks, the nominal exchange rate does not follow a random walk; instead, the exchange rate undershoots its long-run value. An undershooting of the exchange rate derives from the active monetary policy that both countries conduct.
Keywords: E5; F3; F4; 330; Monetary policy rules; open economy macroeconomics; exchange rate